MotionSure: A cloud-based algorithm for detection of injected object in data in motion - Islam, Thouhedul; Olanrewaju, Rashidah Funke; Khalifa, Othman O. (2017 IEEE 4th International Conference on Smart Instrumentation, Measurement and Application (ICSIMA), 2017)
One of the problems in cloud computing data security is injected object during data movement from one state to another. Mostly, the Man In The Middle (MITM) attack happens in this stage by hijacking active session variables, manipulating files and objects. Although there are few algorithms for data protection in the Cloud, However, such algorithms are still prone to attack, especially in real-time data movement due to the mechanism employed. This paper proposes a secure auto-detection of an injected object based on hash function labeling; a one-time security header for transferable files that protects an unauthorized injection. The labeling header allows two-way data binding; DOM based communication between local and cloud computing that triggers automated acknowledgment immediately after file modification. Two encryption functions in PHP has been used for detecting injected object; bcrypt methods in Laravel and MD5 that generate 32 random keys. Total 1600 different type of files were used for evaluation of the proposed algorithm, results show that 87% of injected objects were correctly detected.